Local quantum phase transition in the pseudogap Anderson model: scales, scaling and quantum critical dynamics - Glossop, M; Logan, D (2003)
The pseudogap Anderson impurity model provides a paradigm for understanding local quantum phase transitions, in this case between generalised Fermi liquid (GFL) and degenerate local moment phases. Here we develop a non-perturbative local moment approach to the generic asymmetric model, encompassing all energy scales and interaction strengths and leading thereby to a rich description of the problem. We investigate in particular underlying phase boundaries, the critical behaviour of relevant low-energy scales, and single-particle dynamics embodied in the local spectrum D(ω). Particular attention is given to the resultant universal scaling behaviour of dynamics close to the transition in both the GFL and LM phases, the scale-free physics characteristic of the quantum critical point itself, and the relation between the two.